Six-month Outcome after Early Invasive Versus Delayed Ischaemia Driven Percutaneous Coronary Intervention in Non-ST Elevated Myocardial Infarction - Islam, Rashedul; Ahsan, Syed Ali; Rahman, AKM Fazlur; Zaman, SM mustafa; Khaled, Md Fakhrul Islam; Biswas, Suman Kumar; Ahasan, Mohammad Hasimul; Ansari, Sanjida; Karna, Rajan; Ahmed, Khurshed; et al. (University Heart Journal, 2022)
Background: Optimal timing of PCI and comparative outcome between early invasive strategy and ischaemia guided delayed invasive strategy is still in debate in reducing long-term cardiovascular complications in NSTEMI. Objective: The aim of the study was to assess the impact of an early invasive strategy or ischaemia guided delayed invasive strategy on six months clinical outcomes in NSTEMI patients undergoing PCI, from a Bangladesh health service perspective. Materials and Method: It was an observational cross-sectional comparative study conducted in cardiology department of BSMMU from November 2019 to February 2021. Study procedure: This study enrolled 389 adult patients of NSTEMI who underwent PCI which met inclusion and exclusion criteria. Study subjects were divided into two groups: early and delayed groups. This study considered an early invasive strategy as - revascularization within 72h for patients presented with NSTEMI with high-risk features defined by a GRACE score > 140 and for those at lower risk with GRACE score <140; delayed ischaemia driven strategy as - revascularization after 72h, reserved for refractory, recurrent or severe exercise-induced ischaemia. Coronary angiogram (CAG) and PCI were performed by respective consultant according to current practice guidelines. After index PCI, patients were followed up at 06 months for MACEs (Myocardial re-infarction, target vessel revascularization, stroke, hospitalization due to ischaemic causes and cardiac death) and findings of 2 groups were compared. Results: At 6 months after index PCI, patients in the early group despite having worse initial presentation and higher GRACE score had better outcome in comparison with the delayed group who had a statistically significant higher incidence of cardiac death, MI, and target vessel revascularization (p=0.002, p=0.004 and p=0.031). However, incidence of stroke, major bleeding and hospitalization due to ischemia were not significantly different between the groups (p>0.05). Conclusion: Adoption of an early invasive strategy in NSTEMI patients undergoing PCI may be beneficial in reducing the risk of MACEs and associated with improved clinical outcome after PCI at 6 months follow-up. University Heart Journal 2022; 18(1): 22-28